Paraganglioma-like dermal melanocytic tumor - Anoop Thyvalappil; Bindurani Sudhamani; Geetha Kizhakkethara; Rajiv Sridharan; Robins Kunjan (Wolters Kluwer Medknow Publications, 2015)
Paraganglioma-like dermal melanocytic tumor (PDMT) is a rare subtype of benign dermal melanocytic tumor, first described in 2004. Its histopathologic features resemble those of paraganglioma, showing presence of a distinctive partitioning of the tumor into small and large packets, nests, or short cords by delicate fibrous septa (zellballen pattern). But the immunostaining characteristics are those of melanocytic lesions, as PDMT express S-100, melan A, HMB 45 and lack pancytokeratin markers. It has a benign course, although a lesion of low malignant potential cannot be excluded. We describe a case of 60-year-old female who presented with three PDMT lesions on her right leg. To the best of our knowledge this is the first case reported from India.